F. Scott Fitzgerald’s Die Schönen und Verdammten: A Corpus-based Study of Speech-act Report Verbs as a Feature of Translators’ Style - Winters, Marion (Meta, 2007)
AbstractThe aim of the present paper is to identify features of translators’ style, comparing two German translations of F. Scott Fitzgerald’s The Beautiful and Damned, both published in 1998. Speech-act report verbs are investigated as potential elements of the individual styles of the translators. Corpus analysis is facilitated by the use of corpus processing tools. The paper concludes with comments on the translators’ different usage of repetition versus variation and their effects.